Documenting the subjective patient experience of first versus second cataract surgery. Issue 1 (January 2015) - Adatia, Feisal A.; Munro, Monique; Jivraj, Imran; Ajani, Abdallah; Braga‐Mele, Rosa
Abstract : Purpose : To examine the subjective patient experience after cataract surgery. Setting : Single multisurgeon cataract facility. Design : Prospective intraindividual observational study. Methods : Patients completed a questionnaire immediately after cataract extraction performed in their second eye. All patients had second‐eye surgery within 6 months of first‐eye surgery. Cases longer than 30 minutes were excluded. Results : Of the 292 patients who completed the questionnaire, 12 were excluded based on surgical time. The response rate varied per question. The surgery was rated as taking longer or being more painful in the second eye by 127 patients (45.4%) and in the first eye by 38 patients (13.5%) ( P < .05); 115 patients (41.1%) reported no difference. Patients (47.83%) who rated the second eye as the generally more negative experience thought their vision would be better and 3.48% worse ( P < .05); 48.70% thought it would be the same. No difference was noted in length of surgery ( P = .3) or sedation used ( P = .96). Conclusions : Of 125 patients who rated second‐eye surgery as the generally more unpleasant procedure, 90 (72.0%) were similarly or more relaxed during the second procedure. Second‐eye cataract surgery was perceived as being a longer and/or more painful procedure by a significant number of patients (45.4%), and only 3.48% thought that vision in the second eye would be worse. These results can help surgeons when counseling patients regarding expectations for second surgery. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.